REPRESENTATION OF ISLAMIC VALUES IN THE FILM “PANTASKAH AKU BERHIJAB”: A SEMIOTIC ANALYSIS OF THE CONCEPT OF HIJAB AS A SYMBOL OF SELF-PROTECTION FROM SEXUAL VIOLENCE AMONG STUDENTS - Muzammil Muzammil; Zahrotul Jannah (Journal Analytica Islamica, 2026)
This study aims to analyze the representation of Islamic values in the film Pantaskah Aku Berhijab through Roland Barthes’ semiotic analysis, focusing on the concept of hijab as a symbol of self-protection from sexual violence among students. The study is motivated by the increasing number of sexual violence cases, the importance of Islamic value-based media literacy, and the influence of film as a medium in shaping students’ perspectives and character. This research employs a descriptive qualitative interpretive approach, with data collected through observation of film scenes, documentation, and interviews. The data were analyzed using Roland Barthes’ semiotic theory, which includes denotative, connotative, and mythical meanings. The findings show that the film represents the hijab as an Islamic identity that functions not only as a means of covering the body, but also as a symbol of spiritual transformation, religious awareness, and the formation of Muslim women’s identity. In addition, the hijab is represented as a symbol of self-protection encompassing moral, psychological, and spiritual dimensions, without positioning it as the sole factor in preventing sexual violence. The film also represents Islamic moral values, such as preserving personal honor (hifz al-‘ird), mutual respect, maintaining boundaries in social interactions, responsibility, empathy, and the formation of healthy relationships as part of efforts to prevent sexual violence. This study concludes that Pantaskah Aku Berhijab serves as an educational medium capable of representing Islamic values contextually and contributing to the strengthening of character education, media literacy, and students’ awareness of the importance of preserving personal honor and building healthy social relationships based on Islamic teachings.